Changes in Extreme Climate Events in Rice-Growing Regions Under Different Warming Scenarios in China - Chou, Jieming; Zhao, Weixing; Li, Jiangnan; Xu, Yuan; Yang, Fan; Sun, Mingyang; Li, Yuanmeng (Frontiers in Earth Science, 2021)
Scientific prediction of critical time points of the global temperature rise and assessment of the associated changes in extreme climate events can provide essential guidance for agricultural production, regional governance and disaster mitigation. Using daily temperature and precipitation model outputs from the Coupled Model Intercomparison Project (CMIP6), the time points of the temperature rise by 1.5°C and 2.0°C have been assessed under three different greenhouse discharge scenarios (SSP126, SSP245, SSP585). To characterize the change of extreme climate events in rice growing regions in China, six indices have been designed, and a time slice method is used. An analysis from an ensemble of CMIP6 models shows that under SSP245, the global mean temperature rises by 1.5°C/2.0°C around 2030/2049. A global warming of 2.0°C does not occur under SSP126. The time for a 1.5°C/2.0°C warming all becomes earlier under SSP585. Under a 1.5°C warming, the number of warm days (TX90p), rice heat damage index (Ha), consecutive dry days (CDD), five-day maximum precipitation (Rx5day) and the number of annual total extreme precipitation events (R99pTOT) clearly increase, while the number of cold damage (Cd) events decreases. All the indices show a strong variability regionally. For example, the consecutive dry days (CDD) increases significantly in the Central China and South China rice growing region. The monthly maximum consecutive 5-day precipitation increases by as much as 6.8mm in the Southwest China rice growing region.